Second opinion programmes in Germany: a mixed-methods study protocol. Issue 2 (10th February 2021) - Bruch, Dunja; May, Susann; Prediger, Barbara; Könsgen, Nadja; Alexandrov, Alexander; Mählmann, Sonja; Voß, Karl; Liersch, Sebastian; Loh, Jan-Christoph; Christensen, Bernd; Franzen, Achim; von Peter, Sebastian; et al.
Abstract : Introduction: Second opinion programmes aim to support the patients' decision-making process and to avoid treatments that are unnecessary from a medical perspective. The German second opinion directive, introduced in December 2018, constitutes a new legal framework in statutory health insurance for seeking second opinions for elective procedures and so far includes tonsillectomy, tonsillotomy, hysterectomy and shoulder arthroscopy. The directive mandates physicians who recommend one of the above-mentioned surgeries to inform their patients of their legal right to visit a certified second opinion provider. Since second opinion programmes are a fairly recent phenomenon in Germany, no comprehensive data are yet available on the degree of implementation, users, potential barriers and their effectiveness. We aim to examine the characteristics and the use of second opinion programmes as well as the needs and wishes from the perspective of (potential) users in Germany, with focus on the decision-making process, the patient–physician relationship and the motivation to seek a second opinion, as well as the role of health literacy. Methods and analysis: Six substudies will include the following stakeholders: (1 and 2) patients with one of the four surgery-indications covered by the directive, (3) patients who electively sought an online-based second opinion, (4) patients with oncological diseases, (5) the general population and (6) medical specialists. A mixed-methods approach will be used, including questionnaires, interviews and focus groups. The data will be evaluated using quantitative descriptive analysis and qualitative content analysis. The integration of the results will take place in the form of a triangulation protocol. Ethics and dissemination: The study protocol was approved by the Ethics Committee of the Brandenburg Medical School. The findings will be published in peer-reviewed journals and presented at scientific conferences.